Tinjauan Fenomena “Hate Speech” dengan Muatan Politik di Indonesia dalam Perspektif “Psychological Hatred” - Hanna Rahmi, Hanna Rahmi; Nugraha, Andreas Corsini Widya (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2020)
The birth of social media in Indonesia has positive and negative benefits in the field of information. The problem that arises because of technological developments, especially social media, one of which is hate speech. The “Election” phenomenon of both the President and the Regional Head dragged social media into a stream of negative campaigns and became a lighter for the emergence of “hate speech” in social media. Historically “hate speech” has long appeared and is accompanied by events of violence, abuse, and mass genocide in certain groups of people and communities. This becomes a serious problem if not handled seriously because it is basically the cause of the conflict and the disintegration of the nation. Psychological Studies tries to parse the common thread of the emergence of “hate speech”, so that in the future there are potential ideas in unraveling problems related to hate speech, especially in the field of education.